DT7 peptide-modified lecithin nanoparticles co-loaded with γ-secretase inhibitor and dexamethasone efficiently inhibit T-cell acute lymphoblastic leukemia and reduce gastrointestinal toxicity. (1st May 2022) - Zhou, Ying; Guan, Li; Li, Wei; Jia, Ruinan; Jia, Lejiao; Zhang, Yuanyuan; Wen, Xin; Meng, Sibo; Ma, Daoxin; Zhang, Na; Ji, Min; Liu, Yongjun; et al.
Abstract: T-cell acute lymphoblastic leukemia (T-ALL) is a serious hematologic malignancy and glucocorticoid resistance is the main recurrent cause for a high relapsed and death rate. Here, we proposed an effective therapeutic regimen of combining gamma-secretase inhibitors (GSIs) with dexamethasone (DEX) to overcome glucocorticoid resistance. Moreover, the bone marrow targeting DT7 peptide-modified lecithin nanoparticles co-loaded with DEX and GSI (TLnp/D&G) were developed to enhance T-ALL cells recognition and endocytosis. In vitro cytotoxicity studies showed that TLnp/D&G significantly inhibited cell survival and promoted apoptosis of T-ALL cells. Mechanically, we found that GSIs promoted DEX-induced cell apoptosis by two main synergetic mechanisms: 1) GSIs significantly upregulated glucocorticoid receptor (GR) expression in T-ALL and restored the glucocorticoid-induced pro-apoptotic response. 2) Both DEX and GSI synergistically inhibited BCL2 and suppressed the survival of T-ALL cells. Furthermore, in vivo studies demonstrated that TLnp/D&G showed high bone marrow accumulation and better antileukemic efficacy both in leukemia bearing models and in systemic Notch1-induced T-ALL models, with excellent biosafety and reduced gastrointestinal toxicity. Overall, our study provides new strategies for the treatment of T-ALL and promising bone marrow targeting systems with high transformation potential. Highlights: DT7 peptide-modified lecithin nanoparticles co-loaded with γ-secretase inhibitor and dexamethasone (TLnp/D&G) were developed for the synergistic pro-apoptosis effect mediated by inhibition of Notch1 signaling and repression of BCL2. TLnp/D&G enhanced drug accumulation in bone marrow by promoting the penetration crossing marrow blood barrier as well as actively targeting T-ALL cells. TLnp/D&G abrogated KLF4-induced gastrointestinal toxicity caused by GSIs, showing excellent biosafety and high transformation potential.